Determinan Aktivitas Fisik pada Aggregate Dewasa - Aulia Rahmi; Asniar Asniar; Teuku Tahlil (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the determination of physical activity in adult aggregates in Lhokseumawe City. The research design used was a descriptive correlation with a cross-sectional approach. The results showed that the majority of respondents were adults (26-35 years old) that is 61 people (62.9%), female 69 people (71.1%), higher education level 74 people (76.3%), working does not depend on time, namely, 36 people (37.1%), living in urban areas, namely 90 people (92.8%), and having a monthly income of <Rp 3,165,030, namely 69 people (71.1%). Variables related to physical activity were age (p=0.003), perceived benefits and barriers (p=0.024), and self-efficacy (p=0.000). The most dominant factor about physical activity in respondents was age, with an odds ratio of 4.622 (95% CI: 1.759-12.143). In conclusion, the most significant determinant of physical activity in the adult aggregate is age. Keywords: Aggregate Adults, Determinants of Physical Activity